Production chains in food agroindustrial activity : Arequipa Region - Aranaga Manrique, David (2009)
This work aims to establish the factors that determine the low productivity and weak competitiveness of food agroindustrial activity in the provinces of Castilla, Caylloma, Condesuyos and La Unión in the Arequipa Region, which suffer from strong socioeconomic problems. In order to achieve sustainable economic growth and improve the material living conditions of the population, a feasible alternative is the establishment of productive chains and the promotion of small producers' associativity.